Proximate Composition, Minerals, Heavy Metal And Pesticide Resudues esticide Resudues Of Three Popular Cut-Up Parts Of Commercial Chicken From North 24-Parganas Area, West Bengal est Bengal - Chakraborty, A.; Biswas, S.; Chakraborty, R.; Majumder , D.; Majumder, D.; Chakraborty, A. Dhargupta (Journal of Meat Science, 2014)
Study was conducted to determine the proximate and mineral composition as well as heavy metals and pesticide residues in three popular cut-up parts (drumstick, breast and wing) of commercial chicken. A total number of 120 broiler birds of 35-42 days of age were selected from different areas of North 24-Parganas, West Bengal and the slaughtering and dressing were done as per the standard procedure. The data were analyzed statistically for valued conclusion. Significant (P<0.05) differences were observed among the three cut-up parts in terms of moisture, protein, ether extract and ash content. The mineral contents also differed significantly (P<0.05) and Fe was found highest in breast and Ca, Na and K was highest in drumstick. Amount of Cu did not differ significantly but the amount of Zn differed among the three parts. The amount DDT, though within the permissible limit, was found highest in drumstick part. Pb, Aldrin and Endosulfan was found below the detectable limit.